The interaction of glycosylated major outer membrane protein of Campylobacter jejuni with natural and synthetic ligands - Okoye, Jennifer Chigozie (2021)
According to the WHO fluoroquinolone- resistant Campylobacter jejuni (C. jejuni) is number six on the list of antibiotic-resistant "priority pathogens" – a list of 12 families of bacteria that pose the greatest threat to human health1. C. jejuni is one of the four key global causes of gastrointestinal diseases. Currently, the cost of illness is $1.3billion in the US and €2.4billion in the EU272. There are a large variety of host sources of C. jejuni, but poultry is thought be the major risk factor, as it is the main animal reservoir3. Sustainable and innovative solutions to combat emerging infectious disease through alternative interventions must be encouraged. For the protection of the public, control of zoonosis (a disease which can be transmitted from animals to humans) is important. Processes should include avoiding bacterial colonisation of poultry, hygienic processing of meat and the protection and control of private drinking water supplies. The overarching goal is to reduce the load of C. jejuni in farm poultry to a level with low probability of causing illness to humans. The aim of this project was to study the C. jejuni Major Outer Membrane Protein (MOMP) and its ability to bind to carbohydrate based blood group antigens (BgAgs) and novel compounds in its glycosylated and non-glycosylated forms. Novel compounds include a class of iron (III) compounds. Characterising the porin functionality of MOMP (the role it plays in bacteria and the size of molecules that can be exchanged through this protein) is important to optimise the interactions between glycosylated MOMP and synthetic compounds which inhibit bacterial attachment to surfaces and biofilm formation. We cloned the wild type MOMP encoding gene from C. jejuni NCTC11168 into Escherichia coli (E. coli) to create a novel recombinant protein for purification and subsequent analysis. However, difficulties with MOMP purification from the heterologous host, led to native MOMP being purified directly from C. jejuni. Studies of the C. jejuni 11168 derived wtMOMP showed that the glycan consists of at least 3 monosaccharides with a close similarity to N-galactosamine-galactose-ribose. The EC50 of the binding of Leb with wtMOMP was measured to be 23 nM, conferring to high potency of the BgAgs for the glycosylated protein. Iron (III) compound - QPLEX, which has previously been shown to cause reduction in colonisation of C. jejuni in poultry, favoured binding to glycosylated MOMP over non-glycosylated MOMP in vitro thus inhibiting association of MOMP to Leb. We showed that QPLEX (and to some extent Leb) causes a conformational change of the wtMOMP protein in the transverse region of the protein from the extracellular region extending to the underside of the porin, a conformational change which was further confirmed in protein ligand docking. Binding of QPLEX to the loop region of the porin and within the constriction zone of the porin was highly favourable with CHEMGAUSS scores of -8.5 and -8, respectfully. Finally, localisation of specific binding between wtMOMP and human intestinal gut tissue sections was demonstrated ex vivo with binding occurring especially on the corpus. This was further confirmed with observation of specific binding of wtMOMP on transgenic mouse stomach tissue positive for Leb.